2012
DOI: 10.1111/j.1540-8175.2012.01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Significant Conduction Disease through Noninvasive Assessment of Cardiac Calcification

Abstract: Echocardiographic-based calcium scoring correlates with the presence of severe conduction disease requiring a pacemaker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Degenerative calcification, reflective of either biological or abnormally accelerated aging process of the CV system (such as post‐insult in the latter), plays an inextricable role in the pathogenesis of cardiac conduction disorders (Angelini, Moreolo, Ruffatti, Milanesi, & Thiene, ; Isotalo et al, ; Pillai et al, ). For instance, imaging‐detected global cardiac calcification burden has been shown to correlate with the presence of cardiac conduction deficit and increased risk of pacemaker implantation (Mainigi et al, ). Furthermore, calcification occurring at sites of specific electro‐anatomical relevance, such as the AV node and the His‐Purkinje system, led to AV block (Angelini et al, ) and intraventricular conduction abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative calcification, reflective of either biological or abnormally accelerated aging process of the CV system (such as post‐insult in the latter), plays an inextricable role in the pathogenesis of cardiac conduction disorders (Angelini, Moreolo, Ruffatti, Milanesi, & Thiene, ; Isotalo et al, ; Pillai et al, ). For instance, imaging‐detected global cardiac calcification burden has been shown to correlate with the presence of cardiac conduction deficit and increased risk of pacemaker implantation (Mainigi et al, ). Furthermore, calcification occurring at sites of specific electro‐anatomical relevance, such as the AV node and the His‐Purkinje system, led to AV block (Angelini et al, ) and intraventricular conduction abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, several large population‐based cohorts, such as the Cardiovascular Health Study and the Multi‐Ethnic Study of Atherosclerosis, have shown that atherosclerotic risk factors have an influence on the presence of valvular and aortic root calcification and its impact on increased cardiovascular mortality . Extensive interest in the assessment of extracoronary cardiac calcifications is arising from recent data indicating the relation between valvular and aortic root calcification and conduction disturbance, coronary artery stenosis, coronary atherosclerotic plaques, and myocardial ischemia . Most recently, several studies indicated that the multiple calcium deposits in heart valves improve the predictive power with respect to mortality .…”
Section: Discussionmentioning
confidence: 99%
“…The electrophysiological role of hyperkalaemia in triggering bradyarrhythmias is likely potentiated by the presence of underlying structural abnormalities in the conduction system and/or abnormal cardiac autonomic regulation of the pacemaker activity that prevent adequate heart rate reactions in response to physiological stress. Cardiac valve calcification may affect the cardiac conduction system and has also been implicated in bradyarrhythmias (Mainigi et al, 2012). It is highly prevalent in HD (Matsuo et al, 2018) and peritoneal dialysis (PD) patients (Wang et al, 2003) and has been associated with increased cardiovascular mortality (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%